(untitled) (Informatica, 2021)
This paper focused on understanding the growing demand for consumer-oriented health information technologies (CHITs) wearable and adult healthcare management apps. This study utilised the Technology Acceptance Model (TAM) and integrated the concept of perceived risk. The structural Equation Modelling (SEM) technique was applied to test the research hypotheses based on the 450 quantitative responses. This study confirms significant relationships between perceived usefulness, perceived ease of use, perceived risk, attitude, behavioural intention, and actual intention in using CHITs. The findings also showed no evidence to conclude that age and education influenced respondents perceived usefulness and perceived ease of the CHITs. This study incorporated the perceived risk to fill a gap in the literature and broaden the current TAM theoretical application in the public health setting. The study findings fill the health-related technology acceptance literature gap and broaden TAM’s present application in the public health setting.